Accommodating Disability at University - Cynthia Bruce; M. Lynn Aylward (Disability Studies Quarterly, 2021)
Disabled students in Canadian universities obtain academic accommodations through an individualized service approach. The implementation of these learning supports is dependent on students' ability to navigate institutional policies and procedures that require engagement with faculty who are variably willing to respond. This study documents the experiences of disabled students and their professors as they worked to make these individual arrangements on three Nova Scotia university campuses. Findings centre the relational elements of accommodation procedures and expose their potential to reinforce and naturalize the marginal status of disabled learners while also elucidating the possibility for meaningful systemic change. Findings also situate the student/faculty relationship as an important site of inquiry and analysis for Canadian post-secondary institutions working to become more accessible for a diversity of disabled students.
Keywords: Accommodation; Inclusion; Accessibility; Ableism